POST-ACUTE FUNCTION IN NURSING HOMES RESIDENTS WITH DEMENTIA: A PREDICTIVE MODEL FOR DISCHARGE DISPOSITION - Boltz, M (Innov Aging, 2018)
After hospitalization, the rehabilitative care provided in skilled nursing facilities (SNFs) aims to restore the person to their pre-hospitalization functional status and assist the person to return home. This study used MDS assessment data of individuals (N=22,426), age 65 years and older, admitted to SNFs in 2013 from acute care hospitals in Massachusetts, to develop a predictive model of discharge disposition. Residents discharged to home and other locations demonstrated improved activity in daily living (ADL) function three months after admission to the SNF. A dichotomous logistic regression for predicting remaining in SNF included dementia diagnosis (p<0.0001), severity of cognitive impairment (p=0.0050), ADL function (p<0.0001), age (p<0.0001), gender (p<0.0001), widowed status (p=0.0001), vision loss (p<0.0001), hearing loss (p<0.0001), and delirium (p<0.0001) (ROC curve of 0.68.) Results can be used to identify residents at high risk for remaining at SNF, and can be used to target rehabilitative interventions to promote functional recovery.